Proces riadenia systému kvality sociálných služieb na Slovensku - Šebestová, Petronela (Univerzita Pardubice, 2008)
The contribution is intended for social service workers who deal with the standards of quality in social services and the complex process of systematic development of quality social services. The road to lasting improvement of the quality is characterized by social service facilities at regular intervals, total self-made assumptions on the CAF model.
Keywords: quality; quality assessment; social services; CAF model